Case of Acute Onset Postpartum Paraplegia: Spontaneous Spinal Epidural Hematoma–A Rare Entity - Pandey, Praveen Kumar; Pawar, Inder; Singh, Harsimar (The Surgery Journal, 2019)
Study Design Present study is a case report.Objective This study was to present a rare case of acute postpartum paraplegia due to spontaneous spinal epidural hematoma (SSEH).Background SSEH with incidence rate of 0.1 per 100,000 per year is an extremely rare cause of sudden onset neurological deficit in postpartum patients with no predisposing factors or intrapartum factor causing SSEH resulting in paraplegia.Material and Methods We hereby present our case of acute onset postpartum paraplegia which on magnetic resonance imaging (MRI) shows epidural hematoma around thoracic 12 to lumbar 2 (T12–L2) vertebral regions with adjacent cord changes. MRI is the investigation of choice in such cases which helps in proper timely management of patient. We planned the patient for surgical decompression of hematoma.Results Patient showed rapid reversal of neurological symptoms in postoperative period.Conclusions Acute onset postpartum paraplegia in a healthy female with no significant past history, predisposing factors or intrapartum factors may be caused by SSEH and it should be managed on emergency basis as early and proper treatment has an excellent prognosis as seen in our case.
Keywords: SSEH; postpartum; paraplegia; MRI; decompression